This preview shows page 1. Sign up to view the full content.
29. (a) From
f = c
/
λ
and Eq. 3731, we get
00
11
().
ββ
−−
λ=λ
=λ+∆
λ
++
Dividing both sides by
λ
0
leads to
1
1
=+
−
+
()
.
z
β
We solve for
:
=
+−
=
+
.
2
22
2
2
2
2
z
z
zz
(b) Now
z
= 4.43, so
=
+
=
443
2 443
2
0 934
2
2
..
b
g
b
g
b
g
b
g
(c) From Eq. 4419,
This is the end of the preview. Sign up
to
access the rest of the document.
This note was uploaded on 01/23/2011 for the course ＰＨＹ 214 taught by Professor Timothybolton during the Fall '10 term at Kansas State University.
 Fall '10
 TimothyBolton

Click to edit the document details